Evaluation of Selected Intestinal Damage Biomarkers for the Determination of Intestinal Epithelial Damage in Neonatal Lambs with Diarrhea - Alhallaq, A.; Ok, M. (Tropical Animal Science Journal, 2025)
The aim of this study was to evaluate selected intestinal damage biomarkers for the determination of intestinal mucosal epithelial barrier damage in neonatal lambs with diarrhea. The study material consisted of 68 lambs with diarrhea (experimental group, 39 Escherichia coli infected lambs and 29 Cryptosporidium infected lambs) and 20 healthy lambs (control group) aged between 2 and 20 days. The diseases were diagnosed on the basis of a positive fecal antigen test for E. coli K 99, Rotavirus, Coronavirus, Cryptosporidium, and Giardia species in fecal samples obtained from lambs with diarrhea and clinical signs. In addition, Cryptosporidium oocysts were confirmed by light microscopic examination. Anticoagulated blood samples for hemogram measurements and non-anticoagulated blood samples for biomarker measurements were collected from all the lambs. Serum intestinal fatty acid binding protein (I-FABP), trefoil factor-3 (TFF-3), intestinal alkaline phosphatase (IAP), and claudin-3 (CLDN-3) biomarkers were measured using sheep specific enzyme-linked immunosorbent assay (ELISA) test kits. Standard diarrhea treatment was applied to lambs with diarrhea. While 57 lambs recovered, 11 died. There was a significant increase in serum I-FABP, TFF-3, and IAP concentrations (p<0.001) and a decrease in serum CLDN-3 concentrations (p<0.001) in lambs with diarrhea compared to healthy lambs. Total white blood cell (WBC), granulocyte (GRA), and monocyte (MON) counts increased in lambs with diarrhea compared to healthy lambs (p<0.05). In conclusion, this study demonstrated that I-FABP, TFF-3, IAP, and CLDN-3 were useful and reliable biomarkers to determine the presence and extent of intestinal mucosal epithelial damage in lambs with diarrhea.